Komparasi Hukum Atas Hak dan Kewajiban Buruh menurut UU No 13 Tahun 2003 tentang Ketenagakerjaan dan Undang-Undang No.6 Tahun 2023 tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang No.2 Tahun 2022 tentang Cipta Kerja menjadi Undang-Undang - Shanti Mayasari Aritonang; Akiruddn Ahmad; Zuhri Arif (Universitas Medan Area, 2025)
Labor rights in Indonesia are normatively regulated in Law No. 13 of 2003 concerning Manpower. However, the dynamics of national economic development and demands for an improved investment climate have prompted the enactment of Law No. 6 of 2023 concerning the Stipulation of the Government Regulation in Lieu of Law No. 2 of 2022 concerning Job Creation into law, fundamentally reconstructing labor regulations through an omnibus law approach. The presence of this regulation has sparked legal and sociological debate regarding the extent to which protection of workers' rights and obligations has been strengthened or reduced compared to the previous labor law regime. This study aims to comprehensively analyze the provisions on workers' rights and obligations and the forms of legal protection under Law No. 13 of 2003 and Law No. 6 of 2023. The research method used is normative legal research with statutory, comparative, and analytical approaches. This research was conducted by systematically examining the legal norms governing labor and then comparing the substance of the regulations in both laws to identify similarities, differences, and their legal implications for labor protection. The research findings indicate a significant paradigm shift in the regulation of workers' rights and obligations. The Job Creation Law amends and eliminates several key provisions in the Manpower Law, particularly those related to minimum wages, severance pay, layoffs, outsourcing, leave and rest periods, work duration, the use of foreign workers, social security, and fixed-term contracts (PKWT). From a legal protection perspective, the employment cluster in the Job Creation Law tends to accommodate the interests of business flexibility and economic efficiency, which in turn has implications for reducing the level of normative protection for workers.